Actividad antibacteriana de fracciones del extracto etanólico de la corteza de Swartzia polyphylla (cumaceba) frente a cepas de Staphylococcus aureus y Escherichia coli - Rengifo Rodríguez, Tiffani (2024)
The aim of the research was to evaluate in vitro the antibacterial activity of fractions of the ethanolic extract of Swartzia polyphylla D.C. (cumaceba) bark against strains of Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The research had a quantitative experimental approach, with a factorial design with levels. The ‘Kirby Bauer’ diffusion disc methodology was followed, using meropenem, ciprofloxacin, gentamicin and vancomycin discs as positive controls. The results show that fractions A, B, C and D evaluated against Staphylococcus aureus at a concentration of 1000 mg/mL reported inhibition halos in the range of 15.8 to 16.4 mm that consider the microorganism evaluated as sensitive, and at concentrations of 900 and 800 mg/mL the fractions have an intermediate antibacterial activity. Against Escherichia coli ATCC 25922 at concentrations of 1000, 900, and 800 mg/mL they reported intermediate antibacterial activity with halos of 12.8 to 13.7 mm. The study concludes that the fractions of the ethanolic extract of Swartzia polyphylla D.C. (cumaceba) bark show antibacterial activity against the microorganisms evaluated.